2018
DOI: 10.3389/fneur.2018.00823
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Myxoma and Cerebrovascular Events: A Retrospective Cohort Study

Abstract: Background: Cardiac myxoma (CM) is the most frequent, cardiac benign tumor and is associated with enhanced risk for cerebrovascular events (CVE). Although surgical CM excision is the only curative treatment to prevent CVE recurrence, in recent reports conservative treatment with antiplatelet or anticoagulant agents in high-risk patients with CM-related CVE has been discussed.Methods: Case records at the University Hospital of Tübingen between 2005 and 2017 were screened to identify patients with CM-related CVE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 32 publications
(61 reference statements)
2
70
0
Order By: Relevance
“…1 Neuroimaging studies have demonstrated that ischemic infarction events are the most frequent neurological findings (76.0-88.8%) in patients harboring left atrial myxomas with neurological manifestations. 6,16 In contrast, the exact prevalence of late neurological complications in these patients is unknown because long-term studies evaluating the likelihood of delayed neurological complications have not been conducted. The largest single-center study, by Brinjikji et al, in 47 patients treated for left atrial myxoma, reported that intracranial aneurysm and extravascular "metastasis" represented infrequent neuroimaging findings during the follow up of these patients (observed in 14.9% and 4.3% of cases, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…1 Neuroimaging studies have demonstrated that ischemic infarction events are the most frequent neurological findings (76.0-88.8%) in patients harboring left atrial myxomas with neurological manifestations. 6,16 In contrast, the exact prevalence of late neurological complications in these patients is unknown because long-term studies evaluating the likelihood of delayed neurological complications have not been conducted. The largest single-center study, by Brinjikji et al, in 47 patients treated for left atrial myxoma, reported that intracranial aneurysm and extravascular "metastasis" represented infrequent neuroimaging findings during the follow up of these patients (observed in 14.9% and 4.3% of cases, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Our patient had a CM, which was diagnosed during this hospitalization and confirmed after the surgery. CMs occur most commonly in the fourth to seventh decades [10]. Although they are the most common benign primary heart tumors, they are quite rare.…”
Section: Discussionmentioning
confidence: 99%
“…While waiting for a mass resection surgery in our patient, we initiated an anticoagulant treatment with the antivitamin K. This choice was guided in this context of stroke by the fact that the mass caused an obstacle filling of the ventricle thus promoting the thrombus development. When the time for surgery is long, anticoagulant therapy may be proposed but only has impact on thromboembolic migrations and does not prevent tumor embolism [10].…”
Section: Discussionmentioning
confidence: 99%